Characterization of hydroxyapatite extracted from crab shell using the hydrothermal method with varying holding times - Deni Fajar Fitriyana, .; Rifky, Ismail; Bayuseno, Athanasius Priharyoto; Siregar, Januar Parlaungan; Cionita, Tezara (Tech Science Press, 2024)
Hydroxyapatite (HA) is a bio ceramic commonly utilized in bone tissue engineering due to its bioactive and osteoconductive properties. Crab shells are usually disregarded as waste material despite their significant CaCO3 content, and have not been widely utilized in the synthesis of HA. This study aims to synthesize and analyze HA derived from crab shells using the hydrothermal method with different durations of holding time. This study utilized precipitated calcium carbonate (PCC) derived from crab shells. With a hydrothermal reactor set at 160°C and varying holding times of 14 (HA_14), 16 (HA_16), and 18 (HA_18) h, a PCC and (NH4)2HPO4 mixture was used to synthesize HA. The synthesis results were analyzed using scanning electron microscopy (SEM), fourier transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD) tests. This study has accomplished the synthesis of HA from crab shells. Nonetheless, the final product of synthesis still contained CaCO3 as an impurity. The prolonged hydrothermal holding time of 14 to 18 h resulted in a reduction of impurities while increasing the percentage of crystal weight and crystallite size of HA. Specimen CH_18 is the best-quality product generated in this study. This specimen produced HA with the highest percentage of crystal weight and crystallite size compared to the other specimens. Furthermore, specimen CH_18 exhibited the lowest concentration of impurities. The Ca/P ratio in this specimen was also the closest to 1.67. The Ca/P ratio, crystallite size, and crystal weight percentage of this specimen are 1.54, 19.06 nm, and 99.1%, respectively.